Studi Kasus Kehamilan Risiko Tinggi Ketuban Pecah Dini di RSUD Sukoharjo - Andriani, Riska; - Poltekkes Bhakti Mulia Sukoharjo, Tutik Yuliyanti (IJMS - Indonesian Journal on Medical Science, 2016)
From diagnosaâs writer stack the plan of action andÂ implementation nursing. After doing upbringing nursing during 3x24 hours getting evaluation result for diagnose painful acute, and riks of infection is resolved.Keyword: nursing care, premature rupture of membrane